PIM tools used in a project to foster gender-inclusive business models in small rural enterprises in Honduras - CGIAR Research Program on Policies, Institutions, and Markets (2018)
The PIM-funded gender-sensitive LINK Methodology developed by CIAT is the cornerstone of the Rural Opportunities Project, funded by Global Affairs Canada and implemented by Swisscontact, CIAT, McGill University, and local partners in Honduras. In 2018 Swisscontact rural business advisors were trained in the use of this toolkit, designed to build inclusive commercial relationships linking rural producers with modern markets. It is hoped that this project will allow 450 small rural businesses and 2000 farmers to benefit from gender-inclusive business models.